Edukasi Manajemen Menyusui pada Ibu Hamil sebagai Optimalisasi Pemberian ASI Ekslusif: Education of Breastfeeding Problems and Solutions for Pregnant Women as an Optimization of Exclusive Breastfeeding - Septiana, Yesika Cahya; Larasati, Disa; Putri, Noviyati Rahardjo (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Breast milk or breast milk is the main food source for babies up to 6 months old. Exclusive breastfeeding during the first 6 months of a baby's life has many benefits for the baby, one of which is boosting the immune system. According to data from Riskesdas, in 2018 only 37.3% of babies received exclusive breastfeeding. The failure of exclusive breastfeeding is one of the reasons for the lack of knowledge of mothers about how to breastfeed properly and correctly which can cause breastfeeding problems. The purpose of this community service activity is to increase the knowledge of pregnant women about breastfeeding management including correct breastfeeding techniques, expressed breast milk, breast problems, and solutions while breastfeeding. The service method is carried out by providing education, which begins with a pre-test, then materials and direct practice on how to breastfeed, and ends with a post-test. The result of the service activities is an increase in the knowledge of pregnant women related to correct breastfeeding techniques, breast milk (ASIP), breast problems, and solutions when breastfeeding from before and after education. The knowledge gained by pregnant women can be used as a provision to go through the breastfeeding process so that it can increase exclusive breastfeeding to the baby.